A Comparative Study on Foreign Direct Investment (FDI) in Retail: A Boon or Bane? - Sengupta, Debashish; Titus, Ray (Indian Journal of Marketing, 2011)
India has been termed as a country with most compelling opportunity for retailers’ by AT Kearney’s 2005 Global Retail Development Index. Despite this positivity about the Indian Retail sector and growing organized retailing, FDI in Retail remains a contentious issue. India does not allow FDI in multi-brand retail but permits upto 51 percent in single brand retail and 100 percent in cash and carry wholesale trading. There is a ban on FDI in big multi-brand retail stores, but there is no restriction on companies accessing the foreign equity market through the American and global depository receipts. Whereas many feel that opening up of FDI further would be damaging for the growth of the sector, others feel that it is going to be a shot in the arm for the industry. This paper attempts to capture the shortcoming of the existing retail FDI policy, the claimed boons and banes of further liberalizing retail FDI, the divided industry opinion and finally attempts to analyze the issue itself - that is FDI in retail a blessing or a curse.